Acquired and congenital urethrocutaneous fistula in pediatric population: a tertiary care centre experience - Ghosh, Arindam; Dattaroy, Someshubhra; Barman, Shibsankar (International Journal of Contemporary Pediatrics, 2025)
Background: Urethro- cutaneous fistula in pediatric population is very common after hypospadias surgery ranging from 4-25% in world literature. Other acquired and congenital causes are rare. Successful repair of UCF depends on different technical factors and basic surgical principles. Considering the agony of multiple surgeries in a child and plan after failure is uttermost import and demands more challenge than the primary surgery. We are discussing our experience of UCF management in a tertiary care centre. Methods: The study was conducted during February 2021 to January 2025 in the Department of Pediatric Surgery among 89 boys with urethrocutaneous fistula. Results: Among 89 patients post urethroplasty (84), post traumatic (2), post circumcision (2) and 1 congenital urethrocutaneous fistula was selected. Proximal fistula (46), multiple fistula (18) and 8 among 20 distal fistula patients were repaired with Tunica Vaginalis reinforcement. TV reinforcement resulted in 87.7% success rate and only 9 patients with recurrence. Post circumcision fistula and post traumatic UCF repair is also difficult considering its location. Conclusions: The treatment plan for a fistula must be individualized based on certain variables and basic surgical principles. The significantly improved success rate with the addition of a waterproofing layer suggests the use of this interposition layer should be done at the earliest available opportunity to prevent a reccurnce rather than to reserve it for future options during UCF repair.